2020
DOI: 10.21608/asejaiqjsae.2020.77058
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Particleboard Produced from Some Timber Trees Irrigated with Treated Wastewater

Abstract: This study aimed to manufacture particleboards from Casuarina cunninghamiana (C), Eucalyptus camaldulensis (E), and Pinus halepensis (P) trees irrigated with treated wastewater and their mixtures (E-C, E-P, and C-P) with 50%:50% for each individual raw material. Two urea formaldehyde resin levels (9% and 13%) were used. Modulus of rupture (MOR), modulus of elasticity (MOE), and internal bond strength (IB) as mechanical properties and physical properties (water absorption and thickness swelling) were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Accordingly, soaking in hot or cold water before the cooking process to remove the extractives may improve the properties of the resulting paper. Hassan et al (2020) studied E. camaldulensis and P. halepensis trees that were younger (15 to 16 years-old) than those reported in the current study and prepared for particleboard production. They found that the total extractive content were 9.26% and 3.16% for E. camaldulensis and P. halepensis, respectively, which is lower than the reported values in the current study.…”
Section: Comparison Of Chemical Properties Of Stem and Branch Woodmentioning
confidence: 94%
“…Accordingly, soaking in hot or cold water before the cooking process to remove the extractives may improve the properties of the resulting paper. Hassan et al (2020) studied E. camaldulensis and P. halepensis trees that were younger (15 to 16 years-old) than those reported in the current study and prepared for particleboard production. They found that the total extractive content were 9.26% and 3.16% for E. camaldulensis and P. halepensis, respectively, which is lower than the reported values in the current study.…”
Section: Comparison Of Chemical Properties Of Stem and Branch Woodmentioning
confidence: 94%
“…It grows from 18-45metres tall or taller. The bole is usually straight; when growing in the open it will often branch from low down, otherwise it can be unbranched for more than half the tree's height and from 100-180cm in diameter (Hassan et al, 2020) [23] . This tree is potential of yielding up to 30 tons of biomass on an average per acre per annum of 6-year-old plantation.…”
Section: Introductionmentioning
confidence: 99%